Physicochemical Properties of Warp Knitted Fabrics Colored with Madder and Gall Oak for Sportswear - Recep Karadag; Abdulkadir Pars (Journal of Natural Fibers)
Polyamide/elastane warp-knitted fabrics were separately dyed with gall oak (Quercus infectoria Olivier) and madder (Rubia tinctorum L.). Chromatographic and spectroscopic methods were used to analyze dyed warp-knitted fabrics. A reserved phase high-performance liquid chromatography with the diode-array detection (RP-HPLC-DAD) method was utilized to determine the components of dyes present in the dyed fabrics. Scanning electron microscopy-energy X-ray spectroscopy (SEM-EDX) was utilized for morphological analysis. The undyed and dyed warp-knitted fabrics were characterized by FT-IR. The CIEL*a*b* values of the dyed polyamide-elastane warp-knitted fabrics were measured. Further, in physical testing, the pilling and abrasion resistance of raw and dyed fabrics were examined, and the water contact angle values of all fabrics were measured. Pilling test results were evaluated with a grade of 5 for all fabrics as the best score, and the resistance of fabrics to abrasion was very good. The formation of the fiber-metal-dye complex caused the fabric’s contact angle to drop, giving the fabric a hydrophilic character. The colorfastness characteristics of the dyed fabrics to light, rub, wash, and perspiration have been evaluated. The light fastness scores vary from 3 to 5, and they are satisfactory for using natural dyes to color textiles since they are in the good to moderate range. Overall, the dyed samples displayed a score of 5, which is excellent, on the Gray Scale for washing fastness.